EFEITO DA RADIAÇÃO GAMA NO CONTRÃ”LE DA PODRIDÃO AZUL DOS FRUTOS CÃTRICOS - Ponte, J. Júlio da; Soave, Jaciro; Salgado, Clélio; Carvalho, Paulo C. T. de (REVISTA DE AGRICULTURA, 2016)
EFEITO DA RADIAÇÃO GAMA NO CONTRÃ”LE DA PODRIDÃO AZUL DOS FRUTOS CÃTRICOS